(untitled) (Scientia Agricola, 1993)
Thlastocoris laetus (Hemiptera: Coreidae) is reported for the first time as a pest of pineapple in Brazilian and Peruvian Amazon forest. The damages are commented. The species is characterized and compared with Lybindus dichrous, another coreidbug pest of pineapple in Brazil. The geographical distribution of the two species is reported.